Engaging fashion consumers in social media: the case of luxury brands - Loureiro, S. M. C.; Maximiano, M.; Panchapakesan, P. (International Journal of Fashion Design, Technology and Education, 2018)
The main purpose of the current study is to analyse how desire, perceived self, social values and involvement are related to consumer engagement in the fashion luxury industry. A sample of 295 fashion luxury consumers participate in the study. Findings suggest that desire is the most significant driver of consumer engagement; subjective well-being (SWB) acts as an outcome of consumer engagement; and past experience has an important role in the relationship between engagement and SWB. The article also provides managerial implications, lists out the limitations of current research and offers scope for further research.